Analyzing Indonesian Air Connectivity Period of 2006 - 2016 - Prayoga Nugraha (Journal of the Civil Engineering Forum, 2017)
As an emerging country, Indonesia needs to cope up with recent global development. One of those pivotal elements is arguably the air connection. However, no studies have been found examining Indonesian air connectivity in detail. Deriving from such a situation, this study attempts to analysis the connectivity levels of Indonesia through the period of 2006 and 2016. The study uses the Netscan formulae which entail three elements, namely direct, indirect and hub connectivity. It has been noted that Indonesian connectivity has significantly increased by doubling in size. As a result, the country is relatively well connected in domestic level. Furthermore, many global destinations can be reached thanks to onward connections offered by international gateways with an exception toward Latin America and Central Asia. A contra-productive decision of government concerning designation of main international gateways is also outlined. As these airports mainly located in western part yet their growth is comparatively mature than those are in the eastern part or smaller regions. In terms of airport network, Indonesian airports have greatly raised their hub connectivity by nearly three times. However, these airports have barely been utilized as an intermediate stop for international flights. Finally, this study recommends suggestions to improve the connectivity level from available literature.